Comorbidity indices for clinical trials: adaptation of two existing indices for use with the FREEDOM trial in women with postmenopausal osteoporosis. Issue 1 (January 2016) - Silverman, S.; Wang, A.; Cheng, L.; Yang, Y.; Libanati, C.; Geller, M.; Grauer, A.; Nevitt, M.; Revicki, D.; Viswanathan, H.
Abstract Summary Two comorbidity indices were adapted for use in the FREEDOM trial and significantly correlated with the number of medications and impaired health status at baseline. The indices have applications for the analysis of clinical trial data and would allow for the appropriate adjustment of comorbidities when evaluating clinical trial outcomes. Introduction The purpose of this study is to adapt two published comorbidity indices for use with the FREEDOM clinical trial evaluating postmenopausal women with osteoporosis. Methods FREEDOM enrolled women aged 60–90 years with a bone mineral density T-score <−2.5 at the lumbar spine or total hip and ≥−4.0 at both sites. Comorbidity indices were calculated using methods described by Sangha (Arthritis Rheum 49:156–163, 2003) and Wolfe (J Rheumatol 37:305–315, 2010) following modification. The adapted Sangha index included 12 conditions with a summary score of 0–12; the adapted Wolfe index included 7 conditions with a weighted summary score of 0–8. Higher scores indicated greater comorbidity. A panel of clinicians independently reviewed subjects' medical histories using a systematic process based on Medical Dictionary for Regulatory Activities (MedDRA) preferred terms to map specified comorbid conditions. Spearman correlations between the adapted indices and baseline subject characteristics expected to be associated with comorbidities were examined. Results Of the 7808 subjects in this study, 74 % had ≥1 comorbidities based on the adapted Sangha or Wolfe comorbidity indices. The mean (SD) adapted Sangha and Wolfe comorbidity indices were 1.4 (1.2) and 1.4 (1.3), respectively. Both indices correlated positively with age, body mass index, and the number of medications (r  = 0.54 to 0.55) at baseline and inversely correlated with health-related quality of life (r  = −0.22 to −0.30) (allP  < 0.0001). Further, when either the adapted Sangha or Wolfe index was included as a covariate for assessing mortality over 36 months in the FREEDOM population, the hazard ratio of the comorbidity index indicated that the mortality risk increased by 27 or 28 %, respectively, for each unit increase in the adapted index (bothP  < 0.0001). Conclusions Our work suggests these comorbidity indices may be adapted for use with clinical trial data, thereby allowing for the appropriate adjustment and reporting of covariates in the evaluation of clinical trial outcomes in an osteoporotic population.